2023
DOI: 10.1002/cjce.24876
|View full text |Cite
|
Sign up to set email alerts
|

A review on catalyst development for conventional thermal dry reforming of methane at low temperature

Abstract: Carbon dioxide (CO 2 ) utilization and conversion, as one of the main parts of carbon capture, utilization, and storage (CCUS), is not only considered an important way to mitigate global warming but also an attractive industrial route to produce valuable fuels and chemical feedstocks. Catalytic dry reforming of methane (DRM) is a promising technology for carbon dioxide utilization and conversion as it can produce syngas, carbon monoxide (CO), and hydrogen (H 2 ) for widespread industrial production processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 181 publications
0
4
0
Order By: Relevance
“…79,80 The supports used in most research are Al 2 O 3 , SiO 2 , ZrO 2 , CeO 2 , zeolites, and metal–organic framework (MOF) derived materials. 81 Some novel support materials have been developed in recent years, such as single crystalline metal oxides and crystalline oxides. Song et al 82 designed a Mo-doped Ni DRM catalyst on a single-crystalline MgO support, which showed excellent resistance to sintering and coking with over a reaction time of >850 h. Subsequently, Xiao and Xie 83 established a low-temperature DRM catalyst that operated effectively at 450 °C by anchoring single-crystalline Ni particles on porous single-crystalline CeO 2 monoliths, which led to suitable MSI that improved both catalytic activity and durability.…”
Section: Fundamentals Of Iccu Processesmentioning
confidence: 99%
“…79,80 The supports used in most research are Al 2 O 3 , SiO 2 , ZrO 2 , CeO 2 , zeolites, and metal–organic framework (MOF) derived materials. 81 Some novel support materials have been developed in recent years, such as single crystalline metal oxides and crystalline oxides. Song et al 82 designed a Mo-doped Ni DRM catalyst on a single-crystalline MgO support, which showed excellent resistance to sintering and coking with over a reaction time of >850 h. Subsequently, Xiao and Xie 83 established a low-temperature DRM catalyst that operated effectively at 450 °C by anchoring single-crystalline Ni particles on porous single-crystalline CeO 2 monoliths, which led to suitable MSI that improved both catalytic activity and durability.…”
Section: Fundamentals Of Iccu Processesmentioning
confidence: 99%
“…It is well-known that the high oxygen transport of ZrO 2 provides protection against coke formation . However, it has also been shown that the relatively weak metal–support interactions (MSIs) of Ni with ZrO 2 lead to deactivation by sintering. , To mitigate this effect, Tathod et al deposited a thin layer of MgAlO x MO nanosheets, derived from layer double hydroxide (LDH) NPs, as an intermediate strongly interacting oxide support. This unique hierarchical configuration was shown to provide superior performance and stability in DRM.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Methane conversion produces hydrogen in addition to carbon monoxide, hydrocarbons, or alcohols, which are essential building blocks of the chemical industry. There are different routes to convert methane to hydrogen, including steam reforming of methane (SRM), 7,8 dry reforming of methane (DRM), 9,10 partial oxidation of methane (POM), 11 non-oxidative coupling of methane (NOCM), 12 and catalytic decomposition of methane (CDM). 13 Table 1 summarizes the catalysts and reaction temperatures used in these methods.…”
Section: Introductionmentioning
confidence: 99%